State and nation in African constitutionalism : thematic study - (:unkn) unknown (My University, 2013)
Only the State had a legal personality at the end of the 1789 Revolution. Derived from the phrase "[t] he State is the legal personification of a nation", the above-mentioned personality endows the first (state), to the detriment of the second (the nation), subjective rights. What about after the democratic revolution of 1989, that is to say, some two centuries later? This study attempts to show the revanche of the nation in legal theory from a context in which it was particularly bullied. On the one hand, the nation has a double mediate and immediate representation of the fact that it participates, with an initial legislative power, the formation of the general Will. We also know that the democratic renewal imposed the issue of legitimacy which the nation can control mediately (by the intermediation of the constitutional Court) or immediately (by referendum), the action of other organs including the constituent whose power skill set is framed by the constitution. Investment supranational bodies we discover more and more into the national legal trade makes the question of legitimacy more efficient when the nation, but also its various components (the ability to capture the regional, community or even international Instances), may require the condemnation of the State for breach of legal obligations. The idea of legitimacy is thus assumed for the nation, the opportunity to evaluate the work of state bodies from a large legal system. On the other hand, the constitutional recognition of national diversity and even taking into account the governance of the State profoundly reconfigured the principle of (national) sovereignty maintained by the revolutionary constitutional Law. Based on the principles of personality and territoriality, the African context provides evidence that the nation and sub-national communities are now holders of rights (political, socio-cultural) subjective, which changes the landscape of the modern State. We talk about plural juridic
Keywords: African Research